2017
DOI: 10.1111/pce.12907
|View full text |Cite
|
Sign up to set email alerts
|

The effect of blue light on stomatal oscillations and leaf turgor pressure in banana leaves

Abstract: Stomatal oscillations are cyclic opening and closing of stomata, presumed to initiate from hydraulic mismatch between leaf water supply and transpiration rate. To test this assumption, mismatches between water supply and transpiration were induced using manipulations of vapour pressure deficit (VPD) and light spectrum in banana (Musa acuminata). Simultaneous measurements of gas exchange with changes in leaf turgor pressure were used to describe the hydraulic mismatches. An increase of VPD above a certain thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
4
21
3
Order By: Relevance
“…The data presented in this manuscript show differences between red and blue light effects on stomatal behavior in intact leaves. One immediately obvious distinction is the inhibition of stomatal oscillations by blue light, which was also recently documented in banana leaves (Zait et al 2017). In our study, stomatal oscillations were observed to occur when leaves were illuminated with red light but were absent under blue light.…”
Section: Discussionsupporting
confidence: 77%
“…The data presented in this manuscript show differences between red and blue light effects on stomatal behavior in intact leaves. One immediately obvious distinction is the inhibition of stomatal oscillations by blue light, which was also recently documented in banana leaves (Zait et al 2017). In our study, stomatal oscillations were observed to occur when leaves were illuminated with red light but were absent under blue light.…”
Section: Discussionsupporting
confidence: 77%
“…N = 10 air temperature, influence consistency between measurements [3,18,25]. Instantaneous point measurements under set controlled cuvette conditions generally require a long time for leaves to acclimate to the new conditions within the leaf cuvette [46]. A maximum rate of 30 measurements per day per gas exchange unit has been practically confirmed in environmentally controlled growth chambers [1], and much fewer measurements can be accomplished in field conditions due to the heterogeneity of environmental factors over the day and/or circadian regulation [29].…”
Section: Discussionmentioning
confidence: 99%
“…This ABA-independent response of GC to VPD may be due to the passive-hydraulic response mechanism, which may be attributed to either ancestral regulation that has remained significant in some angiosperm species, including Arabidopsis (McAdam and Brodribb, 2015), or a mechanism that regulates the GC response to a new steady state in bulk leaf turgor (i.e., the new balance between pressures of the GC and epidermal cells; Glinka and Aviv, 1971; Zait et al , 2017). The second possibility could explain GCabi’s larger apertures under ambient conditions (operating close to turgor loss point; Fig.…”
Section: Discussionmentioning
confidence: 99%